Crowds gathering at the ruins of the Opera House on Front St. after a fire, Dawson, Yukon Territory, April 26, 1899 - Hegg, Eric A., 1867-1948 (Hegg and Company, 1899)
Shows the Monte Carlo and the Bank Saloon in the background. Caption on image: "The Opera House in Dawson after the fier. April 26 '99". Klondike Gold Rush.